PENGOLAHAN LIMBAH SEKAM PADI DAN KULIT SINGKONG MENJADI BIOBRIKET DI KELOMPOK TANI NAGARI BATUHAMPAR KABUPATEN 50 KOTA - Elidahanum Husni; Fauzan Ariga; Agung Prananda (Jurnal Hilirisasi IPTEKS, 2024)
Batuhampar is one of the Nagaris located in the Akabiluru District, 50 Kota Regency, West Sumatra Province. Cassava and rice are among the main agricultural products in the Kenagarian Batuhampar. Until now, cassava and rice waste has been either directly disposed of or burned. Waste burning can cause air pollution, while indiscriminate waste disposal can contaminate groundwater and create sanitation problems. Additionally, this waste can also be a source of disease and pose health risks to the local community. Therefore, the utilization of rice husk and cassava peel waste into biobriquettes is a solution to reduce such waste. The objective of this activity is to utilize rice husk and cassava peel waste into biobriquettes in the Nagari Batuhampar Farmer Group, 50 Kota Regency. This activity is conducted through several methods, such as field surveys, biobriquette production, and socialization of the utilization of rice husk and cassava peel waste to farmer groups. This activity took place from July 24th to August 10th, 2023. The final evaluation of the socialization indicates that throughout the activity, the willingness and enthusiasm of the participants to participate and pay attention were quite high. This was observed from the participants who raised questions and provided feedback during the activity. It is hoped that this activity can be continued for farmer groups with different agricultural commodities so that the generated waste can be effectively utilized and contribute to the improvement of farmers' economy.